3-azidotetrahydrofuran-2-carboxylates: monomers for five-ring templated beta-amino acid foldamers? - Watterson, M; Pickering, L; Smith, M; Hudson, S; Marsh, P; Mordaunt, J; Watkin, D; Newman, C; Fleet, G (1999)
Four diastereomeric methyl 3-azidotetrahydrofuran-2-carboxylates were prepared from diacetone glucose as precursors for the synthesis of β-amino acid oligomers with secondary structure.